2021
DOI: 10.3390/antibiotics10111282
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling the Proteins from the exo-xis Region of Lambda and Shigatoxigenic Bacteriophages

Abstract: Despite decades of intensive research on bacteriophage lambda, a relatively uncharacterized region remains between the exo and xis genes. Collectively, exo-xis region genes are expressed during the earliest stages of the lytic developmental cycle and are capable of affecting the molecular events associated with the lysogenic-lytic developmental decision. In Shiga toxin-producing E. coli (STEC) and enterohemorragic E. coli (EHEC) that are responsible for food- and water-borne outbreaks throughout the world, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…The general conclusion from the transcriptomic, proteomic, and metabolomic studies performed in this work is that the exo-xis region facilitates lytic development of the Φ24 B bacteriophage by regulating expression of a battery of phage and host genes involved in the lysis vs. lysogenization decision (especially phage genes c I, c II, and N ), coding for molecular chaperones, and required for metabolism of amino acids, hexoses, and some other compounds, like biogenic amines and acyl carnitines. This corroborates recent predictions about the regulation of gene expression by products of genes included in the exo-xis region, based on use of the AlphaFold and RoseTTAFold machine learning algorithms (Donaldson 2021 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The general conclusion from the transcriptomic, proteomic, and metabolomic studies performed in this work is that the exo-xis region facilitates lytic development of the Φ24 B bacteriophage by regulating expression of a battery of phage and host genes involved in the lysis vs. lysogenization decision (especially phage genes c I, c II, and N ), coding for molecular chaperones, and required for metabolism of amino acids, hexoses, and some other compounds, like biogenic amines and acyl carnitines. This corroborates recent predictions about the regulation of gene expression by products of genes included in the exo-xis region, based on use of the AlphaFold and RoseTTAFold machine learning algorithms (Donaldson 2021 ).…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies suggested that genes from the exo-xis region of lambdoid bacteriophage genome may influence lysogenization and prophage induction processes (Bloch et al 2013 , 2014 ). Further studies led to the hypothesis that proteins encoded in the exo-xis region play roles in transcription, possibly through regulating RNA polymerase (Kwan et al 2013 ; Dydecka et al 2017 , 2018 , 2020 ; Zdrojewska et al 2019 ; Tong et al 2020 ; Donaldson 2021 ). In this light, we investigated global effects of the exo-xis region on gene expression and metabolism in E. coli cells infected with the Stx phage Φ24 B .…”
Section: Discussionmentioning
confidence: 99%
“…However, in the same host strain infected with λ, the opposite result is observed with transcription being the lowest among the exo-xis region genes 10 . In addition to this major difference in gene expression, Stx phage ea22 genes are mosaic 7,10 . To gain a greater understanding of variation among ea22 genes, a previously published dataset of thirty-seven phage and EHEC prophage genomes 24 were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…The Ea22 CTD structure represents the second high-resolution examination of the exo-xis region, the first being the NMR structures of two λ Ea8.5 homologs 6 . A recent review of all exo-xis region proteins predicted by AlphaFold and RoseTTAfold machine learning methods includes a general discussion of Ea22 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present the structure of Orf63 as a first step towards understanding its functional role. This investigation increases the repertoire of exo-xis proteins that have either been modeled or solved to date 14,15 . Through molecular modeling, we have identified a region on Orf63 that can bind a short α-helical ligand.…”
Section: Introductionmentioning
confidence: 97%